RAWLSIAN "JUSTICE" AND THE EVOLUTIONARY THEORY OF GAMES: CULTURAL EVOLUTION AND THE ORIGINS OF THE NATURAL MAXIMIN RULE. - Radžvilas, Mantas (Problems / Problemos, 2011)
This paper is dedicated to the analysis of the maximin principle, which is one of the key theoretical concepts of John Rawls's theory of justice, and the problem that this principle creates for any attempt to provide a naturalistic interpretation of Rawls's concept of fairness. Analysis shows that maximin principle is, in fact, incompatible with the Bayesian decision theory. This paper is intended to show that recent breakthroughs in evolutionary game theory could help to reconcile the maximin principle with a certain naturally emerging and evolutionary stable pattern of human social behaviour.